Tranexamic acid in total hip arthroplasty: Nationwide evidence for reducing blood transfusions and post-operative complications - Hidetatsu Tanaka; Kunio Tarasawa; Yu Mori; Kazuyoshi Baba; Ryuichi Kanabuchi; Yasuaki Kuriyama; Hiroaki Kurishima; Hideki Fukuchi; Hiroki Kawamata; Kiyohide Fushimi; Toshimi Aizawa; Kenji Fujimori (Journal of Joint Surgery and Research, 2025)
Purpose: Total hip arthroplasty (THA) is an effective treatment for hip degenerative diseases; however, peri-operative blood loss often necessitates blood transfusion. Tranexamic acid (TXA) is widely used to reduce bleeding, although limited real-world evidence exists from Japanese populations. This study assessed the association between peri-operative TXA use and transfusion requirements and complications using nationwide data. Methods: THA cases in the Japanese Diagnosis Procedure Combination (DPC) database from December 2011 to March 2023 were retrospectively analyzed. Patients undergoing primary THA for osteoarthritis, osteonecrosis, or rheumatoid arthritis were included. One-to-one propensity score (PS) matching was performed between patients who received TXA and those who did not. Logistic regression was used to evaluate outcomes including allogenic and autologous transfusion rate, infection, deep vein thrombosis (DVT), pulmonary embolism (PE), and death. A subgroup analysis of TXA dosage (≥2000 ​mg vs. <2000 ​mg) was performed. Results: After PS matching, 134,653 patients were included in each group. TXA use significantly reduced allogeneic transfusion on post-operative Day 0 [odds ratio (OR) 0478], Day 1 (OR 0.377), and Day 2 (OR 0.339). Similarly, TXA use significantly reduced autologous transfusion rates on Day 0 (OR 0.555), Day 1 (OR 0.486), and Day 2 (OR 0.533). Higher TXA doses (≥2000 ​mg) further reduced Day 0 allogeneic and autologous transfusions, but increased autologous transfusion risk on Day 1. While no statistically significant differences were found in infection, PE, or death, TXA was associated with a slightly higher DVT risk. Conclusions: Peri-operative TXA use in THA reduced transfusion needs without increasing PE or mortality risks, although careful monitoring for DVT is warranted. Future studies should clarify optimal dosing strategies tailored to Japanese populations.